Improving the Speaking Ability through Role Playing Model in Learning Indonesian Language - Ani Rosidah (Proceedings of The ICECRS, 2019)
This research is motivated by the students' low speaking ability in Indonesian language learning, which aims to improve students' speaking skills through the application of the Role Playing Model. This research is a Classroom Action Research (CAR) carried out in cycles II using a model from Kemmis and MC. Taggart, each action in each cycle consists of four stages, namely planning, action, observation, reflection. This research was conducted at elementary school of Rancagoong, District of Cilaku, Cianjur Regency. The subjects of this study were fourth-grade students, amounting to 24 students, consisting of 13 female students and 11 male students. Data collection techniques used are process tests, observations, interviews, and documentation. The data obtained are in the form of test results as primary data as well as observations, while the interviews and documentation as supporting data. The data analysis technique used is descriptive quantitative analysis. The results of the study show that the use of the Role Playing Model can improve students' speaking ability. This is indicated by an increase in the average value from before the action is taken until the implementation of the cycle II. The average value obtained in cycle 1 after being given action reached 66.88% with a graduation percentage of 54.17%. Then in the cycle II the average value obtained increased to 77.40% with a graduation percentage of 83.33%. In general, it can be concluded that the application of the Role Playing Model can improve students' speaking ability in learning the Indonesian Language in grade IV at Elementary school of Rancagoong, District of Cilaku, Cianjur Regency.